INISIASI MENYUSU DINI DAN BOUNDING ATTACHMENT DALAM PENINGKATAN KESEHATAN SECARA FISIK DAN PSIKIS - Fauziah Nasution, M.Psi (Prodi Kesehatan Masyarakat FKM UIN Sumatera Utara Medan, 2017)
ABSTRACT Early breastfeeding initiation is a breastfeeding process that begins immediately after the baby is born by allowing the baby skin to skin contact for at least the first hour after birth or until the initial feeding process ends. Theoretically, attachment occurs when a baby becomes close to a person or object that gives oral satisfaction. Thus, early breastfeeding initiation is already eligible for attachment formation. In addition, early breastfeeding initiation can improve the physical and psychological health that affects the development of children as an important asset of the state in realizing the quality of human resources and reduce infant mortality and play an important role to maternal health.   Keywords: Initiation of early breastfeeding, attachment, healthy physical, healthy psychic